US-guided high-intensity focused ultrasound in pancreatic cancer treatment: a consensus initiative between Chinese and European HIFU centers - Kun Zhou; Holger Strunk; Dobromir Dimitrov; Joan Vidal-Jove; Maria A. Gonzalez-Carmona; Markus Essler; Chengbin Jin; Zhechuan Mei; Hui Zhu; Milka Marinova (International Journal of Hyperthermia)
Purpose: Ultrasound-guided high-intensity focused ultrasound (USgHIFU) represents a safe and effective non-invasive thermoablative technique for managing inoperable pancreatic cancer. This treatment method significantly alleviates disease-related symptoms and reduces pancreatic tumor volume. However, the current body of evidence is constrained by a lack of randomized controlled trials. The utilization of USgHIFU is primarily indicated for patients with unresectable, locally advanced, or metastatic pancreatic cancer, particularly those experiencing symptoms due to a locally advanced primary tumor.Methods: This collaborative consensus paper, involving European and Chinese HIFU centers treating pancreatic cancer, delineates criteria for patient selection, focusing on those most likely to benefit from USgHIFU treatment. Consideration is given to endpoints encompassing symptom alleviation, local response rates, other oncological outcomes, as well as overall and progression-free survival. Additionally, this paper defines relevant contraindications, side effects, and complications associated with USgHIFU. The publication also explores the feasibility and role of USgHIFU within the context of palliative care, including standard systemic chemotherapy.Results: The non-invasive local treatment of advanced pancreatic cancer using HIFU should be regarded as an adjunctive option alongside systemic chemotherapy or best supportive care for managing this aggressive disease. Based on the ability of USgHIFU therapy to mitigate pain and reduce primary tumor volume, it should be considered as a complementary therapy for symptomatic patients with inoperable pancreatic cancer and as a potential means of tumor debulking. The underutilized yet promising USgHIFU exhibits the potential to enhance patients’ quality of life by alleviating cancer-related pain. Experts in the field should evaluate this treatment option be evaluated by experts in this field, with this consensus paper potentially serving as a guiding resource for the medical community.Conclusions: US-guided HIFU for advanced pancreatic cancer addresses treatment goals, available options, success rates, and limitations. As a non-invasive, effective local therapy, complementary to chemotherapy and best supportive care, it plays a pivotal role in pain relief, reducing of tumor volume, and potentially improving survival rates.